HUBUNGAN PEMBERIAN MP-ASI DENGAN STATUS GIZI USIA 6-24 BULAN DI PEKON WONODADI KABUPATEN PRINGSEWU - Sukma Alvionita; Abdullah Abdullah (Journal Aisyah University, 2026)
One of the most common nutritional problems among toddlers is stunting. Stunting describes chronic nutritional status, identified by a height-for-age (H/A) index with a Z-score ranging from -2 to -3 SD. Based on the SKI results, the prevalence of stunting in toddlers in Pringsewu Regency reached 14.1%, a figure that has not yet reached the 2020-2024 RPJMN target of 14% by 2024. The research objective was to determine the correlation between supplementary feeding (MP-ASI) provision with nutritional status based on height/age (PB/U) or height/age (H/U) of children aged 6-24 months in Wonodadi Village of Pringsewu Regency. This study was conducted in Wonodadi Village. Respondents in this study were all mothers with toddlers aged 6-24 months, with a sample of 57 toddlers. The instruments used were a questionnaire on the provision of complementary feeding and a KIA book. The sampling technique used was total sampling with a purposive sampling method. This research type was quantitative with a cross-sectional approach design, and data analysis used univariate and bivariate analysis. Statistical tests used the gamma test. The study results showed indicate that there is a significant correlation between with a moderate correlation between the provision of complementary feeding and nutritional status based on height/age or height/age (p= 0.027, r= 0.584). Regarding family food security, respondents were advised to use locally available food that could be used as supplemental feeding for kids and to process food more creatively to prevent kids from becoming bored and engaging in the Closed Mouth Movement (GTM). Keywords: Supplementary Feeding, Nutritional Status, Toddlers, Stunting.